The Accounting Of Cryptocurrency As Per Indian Accounting Standards: A Review Paper (Journal of Pharmaceutical Negative Results, 2023)
Crypto currency has become the buzzword these days. Accounting is yet another field where cryptocurrency has occupied its space. In India, the status of accounting for cryptocurrency still remains unclear even though few of the additions have been made in IAS. A list of varied elements exists in the accounting process, where accountants deal in the real world as there is presently no accounting standard regulated for them; one such example is crypto currency. The U.S. GAAP (General Accepted Accounting Principles) and international financial reporting standards (IFRS) has recognized Crypto currency in the present times for public firms as an account for a digital currency as an intangible asset with an unlimited life. Companies will first record crypto on the balance sheet at their cost basis in both scenarios. The goal of this research paper is to assess if there are adequate justifications for the establishment of IFRS accounting rules for crypto-assets (liabilities) and to make suggestions for possible directions in which they may go. A clear insight into the accounting and taxation is attempted in the present research paper.